2014
DOI: 10.1016/j.physleta.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of LiCu2O2 multiferroic compound

Abstract: A spin model of quasi-one dimensional LiCu 2 O 2 compound with ground state of ellipsoidal helical structure in which the helical axis is along the diagonal of CuO 4 squares has been adopted. By taking into account the interchain coupling and exchange anisotropy, the exotic magnetic properties and ferroelectricity induced by spiral spin order have been studied by performing Monte Carlo simulation. The simulation results qualitatively reproduce the main characters of ferroelectric and magnetic behaviors of LiCu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…There are a number of real magnetic materials with one-dimensional or quasi-one dimensional magnetic lattice in which the MEE is realized according to the KNB mechanism [19][20][21][22][23][24][25][26][27][28] . For materials like LiCu 2 O 2 [19][20][21][22] , LiCuVO 4 [23][24][25] , copper halides [26][27][28] and others it is believed that more or less adequate model describing the MEE is believed to be the so-called multiferroic spin chain (MSC), S = 1/2 quantum spin chain with competing ferromagnetic nearest-neighbor and antiferromagnetic next-nearest-neighbor interactions:…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of real magnetic materials with one-dimensional or quasi-one dimensional magnetic lattice in which the MEE is realized according to the KNB mechanism [19][20][21][22][23][24][25][26][27][28] . For materials like LiCu 2 O 2 [19][20][21][22] , LiCuVO 4 [23][24][25] , copper halides [26][27][28] and others it is believed that more or less adequate model describing the MEE is believed to be the so-called multiferroic spin chain (MSC), S = 1/2 quantum spin chain with competing ferromagnetic nearest-neighbor and antiferromagnetic next-nearest-neighbor interactions:…”
Section: Introductionmentioning
confidence: 99%
“…At the present time a number of compounds is known which give evidence of magnetically-driven ferroelectricity and magnetoelectric effect due to KNB mechanism. 2, [7][8][9][10][11][12][13][14] The simplest quantum spin model exhibiting the spiral magnetic order is a spin-1/2 J 1 -J 2 chain with ferromagnetic nearest-neighbor coupling (J 1 ) and antiferromagnetic next-nearest-neighbor coupling (J 2 ) which is considered to be more or less realistic model for such materials as LiCu 2 O 2 , 7-10 LiCuVO 4 , [11][12][13] and CuCl 2 14 to mention just few of them. In the present paper we are going to examine an exactly solvable model exhibiting a nontrivial magnetoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Their data suggest a strong AF 'rung' interaction J 1 and a weak interchain coupling J ⊥ , in contrary to the conclusion obtained by Drechsler et al [13] In this paper, we adopt the suggestion of Masuda et al Our previous study showed that this enhanced antiferromagnetic coupling J 1 would cause a drastic competition with the antiferromagnetic bond J 4 and lead to the modification of the modulated period of the incommensurate spiral order, and more importantly, the thermodynamic behaviors under this condition were in qualitatively good agreement with experimental results. [31] Therefore, according to the exchange parameters from neutron scattering and our previous investigation on this model, the parameters are as follows: J 1 = 3.4, J 2 = −6.0, J 4 = 3.0, and J ⊥ = 0.9. One can note that the ratio |J 4 /J 2 | = 0.5 here is also in the range provided by the experiment.…”
Section: Model and Simulationmentioning
confidence: 99%